The Marine Microalga, Heterosigma akashiwo, Converts Industrial Waste Gases into Valuable Biomass - Stewart, Jennifer J.; Bianco, Colleen M.; Miller, Katherine R.; Coyne, Kathryn J. (Frontiers in Energy Research, 2015)
Heterosigma akashiwo is an excellent candidate for growth on industrial emissions, since this alga has the ability to metabolize gaseous nitric oxide (NO) into cellular nitrogen via a novel chimeric protein (NR2-2/2HbN) and also tolerates wide fluctuations in temperature, salinity, and nutrient conditions. Here, we evaluated biomass productivity and composition, photosynthetic efficiency, and expression of NR2-2/2HbN for Heterosigma growing on simulated flue gas containing 12% CO2 and 150 ppm NO. Biomass productivity of Heterosigma more than doubled in flue gas conditions compared to controls, reflecting a 13-fold increase in carbohydrate and a 2-fold increase in protein productivity. Lipid productivity was not affected by flue gas and the valuable omega-3 fatty acids, EPA and DHA, constituted up to 16 % of total FAMEs. Photochemical measurements indicated that photosynthesis in Heterosigma is not inhibited by high CO2 and NO concentrations, and increases in individual fatty acids in response to flue gas were driven by photosynthetic requirements. Growth rates and maximum cell densities of Heterosigma grown on simulated flue gas without supplemental nitrogen, along with a significant increase in NR2-2/2HbN transcript abundance in response to flue gas, demonstrated that nitrogen derived from NO gas is biologically available to support enhanced CO2 fixation. Together, these results illustrate the robustness of this alga for commercial-scale biomass production and bioremediation of industrial emissions.